Odpowiedzi

2009-12-10T14:25:00+01:00
A) (x - 1) (x + 1)= x² - 1

b) (2 y + 3 z) (2 y - 3 z) = 4 y² - 9 z²

c) (1 + 3 a b) (1 - 3 a b) = 1 - 9 a² b²

d) (x y - m n) (x y + m n) = x² y² - m² n²

e) (1 - √2) ( 1 + √2) = 1 - 2 = -1

f) (√5 - 2) (√5 + 2) = 5 - 4 = 1

g) (√7 + √3) (√7 - √3) = 7 - 9 = -2

h) (2√3 - 1)(2√3 + 1)= 12 - 1 = 11

Pozdro))
2 5 2
2009-12-10T16:23:14+01:00
Zze wzoru (a-b)(a+b)=a²-b²
a) (x-1) (x+1)=x²-1
b) (2y+3z) (2y-3z) =4y²-9z²
c) (1+3ab)(1-3ab) =1-9 a²b²
d) (xy - mn)(xy + mn) =x²y²-m²n²
e) (1-√2)(1+√2) = 1-2 = -1
f) (√5 - 2) (√5 +2) = 5 - 4 = 1
g) (√7 + √3) (√7 - √3) = 7 - 3 =4
h) (2√3 - 1)(2√3 + 1)= 12 - 1 = 11

2 5 2
2009-12-10T20:02:47+01:00
(a-b)(a+b)=a²-b² - liczymy z tego wzoru

a) (x-1)(x+1) = x² - 1
b) (2y+3z)(2y-3z) = 4 y² - 9 z²
c) (1+3ab)(1-3ab) = 1 - 9 a² b²
d) (xy-mn)(xy+mn) = x² y² - m² n²
e) (1-√2)(1+√2) = 1 - 2 = -1
f) (√5-2)(√5+2) = 5 - 4 = 1
g) (√7+√3)(√7-√3) = 7 - 9 = -2
h) (2√3-1)(2√3+1) = 12 - 1 = 11